Predictive biomarkers for cardiometabolic risk in postmenopausal women: insights into visfatin, adropin, and adiponectin - Cybulska, Anna Maria; Schneider-Matyka, Daria; Walaszek, Ireneusz; Panczyk, Mariusz; Ćwiek, Dorota; Lubkowska, Anna; Grochans, Elżbieta; Rachubińska, Kamila; Malewicz, Katarzyna; Chabowski, Mariusz (Frontiers in Endocrinology, 2025)
BackgroundVisfatin, adropin, and adiponectin are involved in many changes associated with obesity and metabolic disorders, and may be related to metabolic syndrome and cardiovascular disease. The selection of visfatin, adropin, and adiponectin as biomarkers is based on their significant roles in metabolic regulation and inflammation, which are critical factors in cardiometabolic risk. Visfatin is known for its pro-inflammatory properties and its ability to modulate insulin resistance. Adropin is involved in energy homeostasis and metabolic health, while adiponectin has anti-inflammatory and insulin-sensitizing effects. During the perimenopausal period, the risk of obesity, and consequently cardiometabolic diseases increases. Therefore, the aim of this study was to assess the relationship between cardiometabolic parameters and circulating levels of visfatin, adropin, and adiponectin in perimenopausal women with regard to their obesity status.Materials and methodsThis study of 168 perimenopausal women utilized a cross-sectional design with non-random sampling. It involved the use of questionnaires, as well as anthropometric and blood pressure measurements. Blood samples were collected to determine the levels of visfatin, adropin, and adiponectin. Statistical analyses, including correlation coefficients, were performed to evaluate the relationship between these biomarkers and cardiometabolic risk factors, such as insulin resistance, lipid profiles, and inflammatory markers.ResultsIn our study, visceral adiposity index and lipid accumulation product negatively correlated with adiponectin levels. Preliminary multivariate linear regression analysis revealed a positive correlation between circulating visfatin and IL-6 levels. Circulating adropin negatively correlated with HbA1C, fasting blood glucose, and insulin. Adiponectin negatively correlated with HbA1C, fasting blood glucose, insulin, and triglycerides. Furthermore, circulating adiponectin positively correlated with HDL, and negatively with HOMA-IR.ConclusionsAdiponectin is a promising biomarker for predicting cardiometabolic risk in postmenopausal women.